Size effects of area extreme pressure for large-scale cladding. (February 2021) - Li, Danyu; Liu, Bin; Zhou, Xiang; Wang, Zhigang
Abstract: Wind pressures at two points on the cladding of a building are not completely correlated. The fully correlated probabilities of the wind pressure on cladding decrease as the scale of the cladding increases. Therefore, a reduction in the area extreme pressure (AEP) is required. In this study, a comparative analysis of the AEP reduction stipulations of the building codes from several countries was initially conducted; the results showed that the applicability of current codes is limited. Subsequently, we determined the effects of AEP reduction on large-scale claddings using the area- and moving-average methods, based on wind tunnel test data. The results indicated that the AEP reduction for large-scale cladding differs at different positions on the roof surface as the reduction at the corners and edges is more significant compared with that at the interior of the roof. The results of the moving-average method exhibited substantial dispersion and uncertainty when the correlation between adjacent measuring points was weak; thus, it is unsuitable for application toward large-scale cladding. Therefore, employing the area-average method, this study proposed different reduction equations for different positions on a roof surface. These equations can be used as a reference for future research and for revising specifications regarding large-scale cladding.